Characterisation of above-ground endophytic and soil fungal communities associated with dieback-affected and healthy plants in five exotic invasive species. (April 2017) - Raghavendra, Anil K.H.; Bissett, Andrew B.; Thrall, Peter H.; Morin, Louise; Steinrucken, Tracey V.; Galea, Victor J.; Goulter, Ken C.; van Klinken, Rieks D.
Abstract: In Australia, several well-established invasive plant species have experienced unexplained dieback. To investigate this issue, we used internal transcribed spacer (ITS) amplicon pyrosequencing to characterise fungal communities within stems (endophytes) and soils associated with dieback-affected and healthy plants from populations of five exotic invasive species ( Jatropha gossypiifolia, Mimosa pigra, Parkinsonia aculeata, Tamarix aphylla and Vachellia nilotica ) across northern Australia. M. pigra and P. aculeata were sampled from multiple geographic regions. A total of 353 and 4926 fungal operational taxonomic units (OTUs) were identified in stem and soil samples, respectively. Members of Ascomycota were common, representing 75% of stem and 49% of soil OTUs. Four common endophytes, including Cladosporium perangustum, were at least 50% more prevalent in healthy than dieback-affected samples for the five invasive species combined. Fungal community structure within stem and soil samples varied among invasive species. For the two species sampled across multiple regions, M. pigra had similar fungal communities within stems among regions, but a significant difference in associated soil fungi, suggesting that host plant rather than environment determined endophytic communities in this species. Irrespective of the invasive species and sample type (stem vs. soil), no significant differences were observed in fungal richness, diversity or community structure between dieback-affected and healthy plants, either locally or regionally. Our work failed to identify fungi that were either unique or relatively more abundant in dieback than healthy plants in these invasive species. Future investigations of biotic factors other than fungi, such as bacteria, archaea and oomycetes, may provide more insights into the mechanism of the dieback phenomenon affecting these species. Highlights: Diverse endophytic and soil fungi present in five invasive species from Australia. Endophytic and soil fungal communities are different for each invasive species. Several endophytes are present in fifty percent more healthy than dieback plants. Similar fungi observed in healthy and dieback plants in the five invasive species. No evidence of specific endophytic or soil fungal taxa associated with the dieback.